De-biasing electric vehicle adoption with personalized nudging - Ursa Bernardic; Davide Cerruti; Massimo Filippini; Jonas Savelsberg; Giuseppe Ugazio (ETH Zurich, CER-ETH - Center of Economic Research, 2024)
Replacing combustion engine vehicles with battery electric vehicles (BEV) is essential to achieving climate objectives and advancing sustainable transportation, aligning with the United Nations Development Goals and the Paris Agreement. In this project, we identify three perception biases linked to EV adoption and address them with personalized non-monetary information treatments to increase the adoption of BEVs among owners of internal combustion engine vehicles. In a randomized controlled trial with 3181 car owners, we measure the extent of perception biases about range anxiety, charging anxiety, and total cost of ownership (TCO). We find that individuals have strong misperceptions related to these three aspects. In a randomized control trial setting, we then introduce three personalized information interventions to correct each of these biases, based on actual driving and parking behavior. Our results show that these treatments, and especially the TCO information treatment, are effective in increasing purchase preferences toward BEVs.
Keywords: 330; Electric vehicle; Innovation acceptance; Consumer preferences; Consumer behavior; Randomized controlled trial; United Kingdom; Elektrofahrzeug; Innovationsakzeptanz; Konsumentenpräferenzen; Konsumentenverhalten; Randomisierte kontrollierte Studie; Großbritannien